2020
DOI: 10.30699/ijmm.14.3.241
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Requirements of a Self-care System on Smartphones for Preventing Coronavirus Disease 2019 (COVID-19)

Abstract: Background: Smartphone applications play a pivotal role in management, providing care and preventing infectious diseases. It also has the potential impact on supportive and self-care. This study aimed to identify the requirements for a smartphones self-care system to prevent corona-virus (COVID-19). Materials & Methods:This was a descriptive study performed in two main stages in 2020. At the first stage, to recognize the requirements for a smartphones self-care system, similar articles were searched and identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…Authors indicated that the completeness of identifying information can ameliorate self-care skills to prevent coronavirus, symptoms management, motivate and decrease stress, and enhance personal hygiene and communication with health care workers. 47 In the current study, “gender, height and weight, and age” had the highest mean score among the demographic characteristics that were in line with the results of studies by Sharp et al, 43 Niakan et al, 46 and Saeedinia. 47…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Authors indicated that the completeness of identifying information can ameliorate self-care skills to prevent coronavirus, symptoms management, motivate and decrease stress, and enhance personal hygiene and communication with health care workers. 47 In the current study, “gender, height and weight, and age” had the highest mean score among the demographic characteristics that were in line with the results of studies by Sharp et al, 43 Niakan et al, 46 and Saeedinia. 47…”
Section: Discussionsupporting
confidence: 91%
“…45 Sharpe and Niakan in their studies emphasized the identifying of demographic information to promote management of people living with HIV. 43,46 In a study by Saeedinia et al, 47 according to the statistical population, 13 data elements were identified for demographic information of a smartphone’s self-care system to prevent COVID-19. Authors indicated that the completeness of identifying information can ameliorate self-care skills to prevent coronavirus, symptoms management, motivate and decrease stress, and enhance personal hygiene and communication with health care workers.…”
Section: Discussionmentioning
confidence: 99%
“…This issue-that the technology required to help older adults often is not understood-is referred to as the "elderly paradox" [10]. Numerous studies have emphasized the importance of user interface design and user experience for all community members to benefit from healthcare apps in the coronavirus era [11,12]. This is because these coronavirus apps must be downloaded by a majority of users to be effective [10].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, maintaining a healthy diet and regular exercise can greatly enhance the immune system's ability to fight against COVID-19 [8]. The content expressed by specialists is of great importance for use in the application and has been incorporated in most self-care research related to the COVID-19 era [9]. On RQ2: The informants in the online workshop helped us to draw the user experience flow and features of the application (MyShield).…”
Section: Discussionmentioning
confidence: 99%